The Effect of Mobile Digital Content Applications Based on Gamification in the Development of Psychological Well-Being - Alhalafawy, Waleed Salim; Zaki, Marwa Zaki (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The aim of this research is to design a proposed model for Mobile Digital Content Applications Based on Gamification and measure its effectiveness in the development of psychological well-being among the graduate students of King Abdulaziz University who are challenged with issues related to the nature of postgraduate studies, which may affect their levels of psychological well-being. Research sample consisted of (62) students, particularly those who are students of the postgraduate programs at King Abdulaziz University. The study has applied the semi-experimental approach that is based on two group design. The experimental group used an application version called "My Academic Advisor", which was developed according to the proposed model, while the control group used a version that did not include any methods or tools for gamification. A measure of psychological well-being was built through the mobile digital content applications. The measure in its final version consisted of 6 themes that included (36) indicators of psychological well-being; 6 indicators for each theme. The results of the application showed the effectiveness of the proposed model of the gamification in the development of psychological well-being among the experimental group students compared to the students of the control group.